Intelligence, emotional intelligence, and emo-sensory intelligence: Which one is a better predictor of university students’ academic success? - Pishghadam, Reza; Faribi, Maryam; Kolahi Ahari, Mahtab; Shadloo, Farzaneh; Gholami, Mohammad Javad; Shayesteh, Shaghayegh (Frontiers in Psychology, 2022)
The primary aim of this study was to determine the role of psychometric intelligence (IQ), ‎emotional intelligence (EQ), and emo-sensory intelligence (ESQ) in university students’ academic ‎achievement. To this end, 212 university students at different academic levels, composed of 154 ‎females and 58 males, were asked to complete the Raven’s Progressive Matrices, the Bar-On ‎Emotional Quotient Inventory, and the Emo-Sensory Intelligence Scale. Data were then matched ‎with students’ Grade Point Averages as a measure of their academic achievement. The results ‎revealed that students’ level of IQ and EQ could positively predict their academic achievement. ‎In the case of their ESQ level, its auditory sub-component was found to be a positive predictor ‎of academic success. Results were discussed, and possible implications and applications for ‎increasing students’ chances for success were presented.‎